THE CONTRIBUTION OF GRIP STRENGTH AND WAIST FLEXIBILITY ON THE ACCURACY OF FLAT SERVICE FOR TENNIS PLAYERS OF PTL UNP (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2016)
Problem of this research was derived from the observation which the researcher found in the field whether in training or competition. There are still many tennis players not able to do the flat service well and properly. This can be seen from theresult of flat service done less maximum. The purpose of the research was to find out how big the contribution of the grip strength and waist flexibility on the accuracy of flat service for tennis players of PTL UNP.Type of the research was correlational research. The population of the research was all tennis players of PTL UNP which consisted of 35 people. The sample in this research was taken by using purposive sampling in which it was taken based on the purpose or the research need. Therefore, the sampel of the research was male players who followed a training in the tennis training club of UNP. They are around 18-24 years old that totaled 20 people. This research was done at PTLUNP club. The grip strength data of PTL UNP tennis players were taken by using hand grip dynamometer test. The waistflexibility data were taken by flexiometer test and the accuracy of flat service data were taken from the playersaccuracy o f flat service.Based on the data analysis, some results were obtained: (1) there was a contribution between the grip strength and the accuracy of flat service , in which the contribution was 62.1%. (2) there was a contribution between the waist flexibility an d the accuracy of flat service , in which the contribution was 62.1%. (3) there was a contribution between the grip strength and waist flexibility on the accuracy of flat service, in which the contribution was 68.3%. It can be concluded that the gripstrength and waist flexibility contribute on the accuracy of flat service.